2017
DOI: 10.1080/14719037.2017.1383783
|View full text |Cite
|
Sign up to set email alerts
|

Trapped in the hierarchy: the craft of Dutch city managers

Abstract: The position of top public managers implies management in three directions: up (political office holders), down (creating organizational capacity), and out (boundary spanning). We know however, little about what these managers do. I present a close-up analysis of city managers using diary analysis, shadowing, and interviews with stakeholders. The analysis interprets their craft as managing up, down, and out. It finds that despite the contemporary emphasis on collaborative public management, the prevalence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Torfing and Ansell (2017) argue that collaboration across traditional boundaries weakens the link between politicians and their administrations because collaboration depends on horizontal relationships that politicians cannot steer vertically (see also Schedler, 2003;Torfing and Triantafillou, 2013). This gives rise to questions of who gives strategic direction in organizations influenced by NPG principles (Torfing et al, 2012;Van Dorp, 2017). For public managers, this increases the ambiguity of managing public organizations (Cloutier et al, 2017).…”
Section: Theoretical Framework: Public Managers In the Purple Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Torfing and Ansell (2017) argue that collaboration across traditional boundaries weakens the link between politicians and their administrations because collaboration depends on horizontal relationships that politicians cannot steer vertically (see also Schedler, 2003;Torfing and Triantafillou, 2013). This gives rise to questions of who gives strategic direction in organizations influenced by NPG principles (Torfing et al, 2012;Van Dorp, 2017). For public managers, this increases the ambiguity of managing public organizations (Cloutier et al, 2017).…”
Section: Theoretical Framework: Public Managers In the Purple Zonementioning
confidence: 99%
“…By answering calls for more research into what public managers do (Chackerian and Mavima, 2001;Dargie, 1998;Van Dorp, 2017), this study contributes to the public management literature by illustrating how public managers in a Swedish city manage their day-to-day affairs in relation to politicians -in other words, how they navigate the purple zone. We also advance our understanding of collaborative organizations by considering the role of political steering (Agranoff, 2006;Torfing and Ansell, 2017) in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, information about environmental contingencies and their transitions have been regarded as crucial to organizational decision makers so that they may take decisions in light of these environmental contingencies (see Katz and Kahn 1966). Hence, this literature has identified boundary spanners as actors that engage in transmission dynamics and act as information exchange agents between an organization and its environment, thus transferring environmental dynamics into their organization (Whetten and Aldrich 1979;Tushman and Scanlan 1981;Leifer and Delbecq 1978;Rosenkopf and Nerkar 2001;Van Dorp 2018). Boundary spanning activities include processing and transmitting of information and externally oriented gatekeeping: the acquirement and maintenance of resources and legitimacy (Adams 1976;Aldrich and Herker 1977; see also Williams 2002Williams , 2013Van Dorp 2018).…”
Section: Theoretical Framework: Boundary Spanning In Digitalization Labsmentioning
confidence: 99%
“…Hence, this literature has identified boundary spanners as actors that engage in transmission dynamics and act as information exchange agents between an organization and its environment, thus transferring environmental dynamics into their organization (Whetten and Aldrich 1979;Tushman and Scanlan 1981;Leifer and Delbecq 1978;Rosenkopf and Nerkar 2001;Van Dorp 2018). Boundary spanning activities include processing and transmitting of information and externally oriented gatekeeping: the acquirement and maintenance of resources and legitimacy (Adams 1976;Aldrich and Herker 1977; see also Williams 2002Williams , 2013Van Dorp 2018). Following the new institutionalist turn in organization research, boundary spanners were later characterized as 'conduit[s] to disseminate ideas and innovations throughout an organizational field' (Galaskiewicz and Wasserman 1989: 456; see also Guarneros-Meza and Martin 2016).…”
Section: Theoretical Framework: Boundary Spanning In Digitalization Labsmentioning
confidence: 99%
“…They are also dealt with in other -more everyday -organizational processes, such as investment planning, budgeting, and political decision-making. Second, scholars that did embrace a broader perspective to capture all sorts of everyday practices, especially aimed to grasp what managers actually do, and reveal how managers spend their time (Mintzberg, 1973;Rhodes et al, 2007;van Dorp, 2018). Mintzberg's landmark study 'The Nature of Managerial Work ' (1973) underlines the tension between the short and long term, as it revealed that managers spend little time on dealing with long-term issues.…”
Section: Introductionmentioning
confidence: 99%